Doping with Rare Earth Elements and Loading Cocatalysts to Improve the Solar Water Splitting Performance of BiVO4 - Meng Wang; Lan Wu; Feng Zhang; Lili Gao; Lei Geng; Jiabao Ge; Kaige Tian; Huan Chai; Huilin Niu; Yang Liu; Jun Jin (Inorganics, 2023)
BiVO4 is a highly promising material for Photoelectrochemical (PEC) water splitting photoanodes due to its narrow band gap value (~2.4 eV) and its ability to efficiently absorb visible light. However, the short hole migration distance, severe surface complexation, and low carrier separation efficiency limit its application. Therefore, in this paper, BiVO4 was modified by loading CoOOH cocatalyst on the rare earth element Nd-doped BiVO4 (Nd-BiVO4) photoanode. The physical characterization and electrochemical test results showed that Nd doping will cause lattice distortion of BiVO4 and introduce impurity energy levels to capture electrons to increase carrier concentration, thereby improving carrier separation efficiency. Further loading of surface CoOOH cocatalyst can accelerate charge separation and inhibit electron–hole recombination. Ultimately, the prepared target photoanode (CoOOH-Nd-BiVO4) exhibits an excellent photocurrent density (2.4 mAcm−2) at 1.23 V versus reversible hydrogen electrode potential (vs. RHE), which is 2.67 times higher than that of pure BiVO4 (0.9 mA cm−2), and the onset potential is negatively shifted by 214 mV. The formation of the internal energy states of rare earth metal elements can reduce the photoexcited electron–hole pair recombination, so as to achieve efficient photochemical water decomposition ability. CoOOH is an efficient and suitable oxygen evolution cocatalyst (OEC), and OEC decoration of BiVO4 surface is of great significance for inhibiting surface charge recombination. This work provides a new strategy for achieving effective PEC water oxidation of BiVO4.